Soil carbon dynamics in the temperate Himalayas: Impact of land use management - Kumar, Shamal Shasang; Wani, Owais Ali; Mir, Shakeel Ahmad; Babu, Subhash; Sharma, Vikas; Chesti, Majeed Ul Hassan; Baba, Zahoor Ahmad; Sofi, Parvaze Ahmad; Wani, Fehim Jeelani; Dar, Shahnawaz Rasool; Singh, Raghavendra; Yadav, Devideen (Frontiers in Environmental Science, 2022)
Food security and environmental health are directly linked with soil carbon (C). Soil C plays a crucial role in securing food and livelihood security for the Himalayan population besides maintaining the ecological balance in the Indian Himalayas. However, soil C is being severely depleted due to anthropogenic activities. It is well known that land use management strongly impacted the soil organic carbon (SOC) dynamics and also regulates the atmospheric C chemistry. Different types of cultivation practices, i.e., forest, plantations, and crops in the Kashmir Himalayas, India, has different abilities to conserve SOC and emit C in the form of carbon dioxide (CO2). Hence, five prominent land use systems (LUC) (e.g., natural forest, natural grassland, maize-field-converted from the forest, plantation, and paddy crop) of Kashmir Himalaya were evaluated to conserve SOC, reduce C emissions, improve soil properties and develop understanding SOC pools and its fractions variations under different land use management practices. The results revealed that at 0–20 cm and 20–40 cm profile, the soil under natural forest conserved the highest total organic carbon (TOC, 24.24 g kg−1 and 18.76 g kg−1), Walkley-black carbon (WBC, 18.23 g kg−1 and 14.10 g kg−1), very-labile-carbon (VLC, 8.65 g kg−1, and 6.30 g kg−1), labile-carbon (LC, 3.58 g kg−1 and 3.14 g kg−1), less-labile-carbon (VLC, 2.59 g kg−1, and 2.00 g kg−1), non-labile-carbon (NLC, 3.41 g kg−1 and 2.66 g kg-1), TOC stock (45.88 Mg ha−1 and 41.16 Mg ha−1), WBC stock (34.50 Mg ha−1 and 30.94 Mg ha−1), active carbon pools (AC, 23.14 Mg ha−1 and 20.66 Mg ha−1), passive carbon pools (PC, 11.40 Mg ha−1 and 10.26 Mg ha−1) and carbon management index (CMI, 100), followed by the natural grassland. However, the lowest C storage was reported in paddy cropland. The soils under natural forest and natural grassland systems had a greater amount of VLC, LC, LLC, and NLC fraction than other land uses at both depths. On the other hand, maize-field-converted-from-forest-land-use soils had a higher proportion of NLC fraction than paddy soils; nonetheless, the NLC pool was maximum in natural forest soil. LUS based on forest crops maintains more SOC, while agricultural crops, such as paddy and maize, tend to emit more C in the Himalayan region. Therefore, research findings suggest that SOC under the Kashmir Himalayas can be protected by adopting suitable LUS, namely forest soil protection, and by placing some areas under plantations. The areas under the rice and maize fields emit more CO2, hence, there is a need to adopt the conservation effective measure to conserve the SOC without compromising farm productivity.